ANALISIS RANTAI NILAI DAN MODEL BISNIS CANVAS GULA AREN DI KECAMATAN DANGIA KABUPATEN KOLAKA TIMUR (Value Chain Analysis And Business Model Canvas Of Palm Sugar In Dangia District, East Kolaka Regency) - MAULANA, AKHMAD; ROSMALAH, SITTI; MA’MUN, SITTI RAHMA; TAO, HAERUDIN (Universitas Mulawarman (University of Mulawarman), 2025)
The purpose of this study was to map the palm sugar value chain in Dangia District, East Kolaka Regency and to identify the palm sugar business model in Dangia District, East Kolaka Regency. The sample in this study was palm sugar processors in Dangia District, as many as 5 palm sugar producers and 3 collectors, 3 wholesalers, 15 retailers. Data analysis used value chain analysis according to the Laundy approach in the link methodology. The results of the analysis showed that the palm sugar value chain in Dangia District has similarities, namely palm sugar producers only have 3 marketing channels, namely consumers, retailers and collectors. Each of these markets can provide different profits after being reduced by production costs (Rp11,200) namely for consumers Rp3,800, retailers Rp5,800 and collectors 3,800. The similarity in getting profits from consumers and collectors is due to the consumer factor, generally the buyers are neighbors around the house or family while the collectors are due to the purchase volume factor which is larger than the others. Retailers are buyers who buy palm sugar with the aim of reselling it and the volume is smaller than the collectors. The retailers then sell it to consumers and the collectors sell it to wholesalers. Wholesalers resell it to retailers and then the retailers sell it to consumers.